Tracing tourism business research trends in Scopus-indexed journals using corpus-based and judgement-based approaches - Laosrirattanachai, Piyapong; Laosrirattanachai, Piyanuch (Humanities, Arts and Social Sciences Studies, 2025)
Tourism research trends reveal the directions of research in the tourism industry contributing to the advancement and modernisation of research frameworks, avoiding delays, and generating academic benefits. This study proposed an alternative approach for analysing research trends in tourism. The proposed analytical approach integrated both corpus-based and judgement-based methodologies, offering an additional means of tracking trends in tourism research and complementing traditional statistical methods, systematic reviews, and bibliometric analyses. To conduct our analysis, we utilised the Tourism Research Abstract Corpus (TRAC), which comprises language data from research abstracts published in the top-10 Scopus-indexed journals in the first quartile (Q1) from 2013 to 2022, totalling 8,304 research abstracts containing 1,352,388 running words. The corpus-based approach involving keyword analysis, lexical profiling, and lemmatisation was applied to identify the major trends in tourism research. Subsequently, we utilised the judgement-based approach involving common and irrelevant keyword removal, as well as theme categorisation, to further elucidate these trends. Our findings highlighted keywords reflecting trends in tourism research each year, categorised into five themes: research topics, research intentions, related concepts, research participants, and research methods. Researchers should take into account these insights when designing studies, adapting methodologies, and in keeping abreast of evolving trends in the discipline.